Wybrane właściwości osadów poflotacyjnych ze zbiornika "Konrad" nr 1 w Iwinach z uwzględnieniem ich przydatności do rekultywacji biologicznej = Selected properties of after-flotation wastes from "Konrad" no 1 reservoir in Iwiny with regard to their utility for biological reclamation - Gawron, Magdalena; Chodak, Tadeusz; Szerszeń, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The reclamation of dumping sites of wastes after floatation of copper ores is a very difficult undertaking. The after-flotation wastes are disadvantageous ground for vegetation of the majority of plants, which is attested by the lack of plant settling on these objects ? even tens years after their excluding from exploitation. The selected physical, chemical and physical-chemical proprieties of after-flotation wastes, that were settled in the reservoir Konrad No. 1 ? adherent to the inoperative KONRAD Miner Institution in Iwiny ? were introduced in the paper. On the basis of the research a trial of evaluation of the analysed wastes' susceptibility to reclamation was undertaken.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); osady poflotacyjne; właściwości fizyko-chemiczne i chemiczne; rekultywacja; after-flotation wastes; chemical and physical-chemical proprieties; reclamation area